Nonlinear Vibration of a Continuum Rotor with Transverse Electromagnetic and Bearing Excitations - Haiyang Luo; Yuefang Wang (Shock and Vibration)
The nonlinear vibration of a rotor excited by transverse electromagnetic and oil-film forces is presented in this paper. The rotor-bearing system is modeled as a continuum beam which is loaded by a distributed electromagnetic load and is supported by two oil-film bearings. The governing equation of motion is derived and discretized as a group of ordinary differential equations using the Galerkin's method. The stability of the equilibrium of the rotor is analyzed with the Routh-Hurwitz criterion and the occurrence of the Andronov-Hopf bifurcation is pointed out. The approximate solution of periodic motion is obtained using the averaging method. The stability of steady response is analyzed and the amplitude-frequency curve of primary resonance is illustrated. The Runge-Kutta method is adopted to numerically solve transient response of the rotor-bearing system. Comparisons are made to present influences of electromagnetic load, oil-film force and both of them on the nonlinear vibration response. Bifurcation diagrams of the transverse motion versus rotation speed, electromagnetic parameter and bearing parameters are provided to show periodic motion, quasi-periodic motion and period-doubling bifurcations. Diagrams of time history, shaft orbit, the Poincaré section and fast Fourier transformation of the transverse vibration are presented for further understanding of the rotor response.